1981
DOI: 10.7164/antibiotics.34.28
|View full text |Cite
|
Sign up to set email alerts
|

Esters and amides of Edeine A.

Abstract: Methods for the synthesis of esters and amides of edeine A were developed and a number of derivatives of this type was obtained and characterized. The antimicrobial activities of the derivatives are comparable to the activity of the native antibiotic and indicate that the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Edeines are pentapeptides with a unique backbone, composed of a glycine, four nonproteinogenic amino acids and a C‐terminal polyamine (spermidine in edeine A 1 and guanyl‐spermidine in edeine B 1 ) (Fig. 1) (Mazerski et al ., 1981; Czerwinski et al ., 1983; Gumieniak et al ., 1983). The biosynthesis of natural products has advantages over chemical synthesis in laboratories due to its low cost and high intensity (Kunga Sugumaran et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Edeines are pentapeptides with a unique backbone, composed of a glycine, four nonproteinogenic amino acids and a C‐terminal polyamine (spermidine in edeine A 1 and guanyl‐spermidine in edeine B 1 ) (Fig. 1) (Mazerski et al ., 1981; Czerwinski et al ., 1983; Gumieniak et al ., 1983). The biosynthesis of natural products has advantages over chemical synthesis in laboratories due to its low cost and high intensity (Kunga Sugumaran et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the unique biological properties of these peptides (the immunological activity and the capacity for universal inhibition of protein biosynthesis) and the difficulties in the chemical synthesis of natural antibiotics, we undertook the synthesis of edeine analogues with simplified structures. It was previously demonstrated that the presence of the free ionizable carboxyl group in the (2R,6S,7R)-A 2 ha moiety was not essential for the biological activity of edeines [20,21]. As a continuation of our research project [22], we recently synthesized the following edeine antibiotic analogues ( Compounds 1-4 were shown to exhibit significantly diminished antibacterial and antifungal activities [22], and they did not display toxic effects towards mammalian cells [23].…”
Section: Introductionmentioning
confidence: 99%